The impact of diverse measures of default risk on UK stock returns - Chen, Jie; Hill, Paula (Journal of Banking & Finance, 2013)
A number of recent papers examine the relationship between default risk and equity returns, and the results are mixed. These studies employ different measures of default risk and we find that correlations between eight diverse measures of default risk tend to be less than 50%. Nonetheless, we find that the relationship between stock returns and diverse measures of default risk tends to be consistent; default risk is a significant determinant of stock returns and this relationship is “hump backed”, as predicted by Garlappi and Yan (2011).